Respiratory changes related to prematurity in neonatal intensive care - Francieli Cristina Krey; Joseila Sonego Gomes; Eliane Raquel Rieth Benetti; Cibele Thomé da Cruz; Mariléia Stübe; Eniva Miladi Fernnades Stumm (Universidade Federal do Ceará, 2016)
Objective: to identify respiratory clinical changes in preterm newborns hospitalized in the Neonatal Intensive Care Unit. Methods: this is a documentary research with 145 medical records by an instrument with sociodemographic variables of preterm newborns and their mothers. Results: most of the newborn were male, 66.9% were born surgically, 64.8% were moderately premature, and the birth weights were between 1,500 and 2,500 grams. Among the respiratory changes, there were early respiratory dysfunction, hyaline membrane, and apnea. There was the prevalence of women in preterm labor (42.8%), water breaking (32.4%) and pre-eclampsia (20.7%) among others were found to be related to obstetric factors related to prematurity. Conclusion: a high incidence of preterm births was observed, with significant respiratory changes.